Physician Perception of Grade Group 1 Prostate Cancer - Saoud R. (2023)
Background: Despite its low-risk nature, grade group 1 (GG 1) prostate cancer (PCa) remains overtreated. This suggests a disconnect between daily physician practice and the standard of care. We hypothesized that GG 1 disease is overtreated because of common misconceptions regarding its true natural history. Objective: To survey physicians worldwide to better understand their approach to management of GG 1 PCa. Design, setting, and participants: A 17-question survey was sent to urology, radiation oncology, and pathology societies on six continents, and was posted on Twitter. Responses were collected and analyzed. Outcome measurements and statistical analysis: Pearson's χ2 test was used to assess correlation between physician-related variables and the perception of active surveillance (AS) for GG 1 PCa. Logistic regression was used for multivariable analysis. Statistical analysis was performed using SPSS version 21. Results and limitations: Among 1303 participants, 55% were urologists, 47% had completed fellowship, and 49% practice in an academic setting. Among the clinicians, 724 (83%) routinely recommend AS for GG 1 PCa and have never/rarely regretted it, while 18 (2%) “often” regretted it. Routine AS was more common among physicians aged <40 yr, those in practice for <10 yr, and those living in North America, Europe, or Australia/New Zealand. More than one-third of the respondents practicing in nonacademic settings reported 15-yr PCa mortality in low-risk PCa of >3%. Regarding reclassification of GG 1 to a precancerous lesion, 428 (39%) felt that this is a good idea, 340 (31%) disagreed, and 323 (30%) were uncertain. Those in support were more likely to be aged <40 yr (p = 0.001), in practice for <5 yr (p = 0.005), urologists (p < 0.001), and fellows trained in urologic oncology (p < 0.001). Opposition was common among pathologists (61%). Among terminologies proposed to replace “cancer” for GG 1 are neoplasm of low malignant potential (51% approval), indolent neoplasm rarely requiring treatment (23%), and indolent lesion of epithelial origin (8%). Conclusions: AS is more commonly recommended by physicians who are younger, are fellowship-trained in urologic oncology, practice in academic settings, and are based in North America, Europe, or Australia/New Zealand. Misconceptions regarding AS outcomes may hinder its adoption. Frequent use of AS is associated with support for changing the “cancer” nomenclature. Patient summary: In this study, we found that active surveillance remains underused in the management of low-risk prostate cancer because of incorrect perceptions regarding cancer outcomes. Omitting the word “cancer” for low-risk lesions is a challenging but promising effort that is favored by many clinicians, particularly by those who advocate for active surveillance.